Comparing mobile banking and internet banking in indonesia based on technology acceptance mobile & security factor - Situmorang, James Rianto (Jurnal Ekonomi, 2024)
The emergence of the Internet is an opportunity for banks in Indonesia to provide internet banking and mobile banking services. Internet banking and mobile banking users increased when the Covid-19 pandemic hit Indonesia because people were encouraged to do their activities from home. Based on data from Bank BCA, Bank BNI, and Bank Mandiri, the number of mobile banking users is more than internet banking users. Some factors customers consider to become internet banking and mobile banking users are the Technology Acceptance Model (TAM) and Security Factor (SF). This study aimed to determine how much influence TAM & SF have on customers' mobile and internet banking decisions. The research method is quantitative with statistical tests using SPSS 25 software. The total sample size is 220 people, of which 110 people are for mobile banking research and 110 people are for internet banking research. The results of the study show that TAM & SF have a positive effect on customers' decisions to use mobile banking as well as internet banking. The number of mobile banking users is greater than internet banking users as evidenced by R21 > R22.